Outcome Evaluation in Social Context Measured by Event-Related Potentials Is Partially Dependent on the Partner’s Sex - Liu, Jinping; Wang, Shurui; Jia, Zhenbiao; Zhang, Entao; Yao, Mengping (Frontiers in Psychology, 2018)
Outcome evaluation is a cognitive process that people rely on feedback information to evaluate behavior results. It can help people to modify the previous mistakes in order to facilitate the performance of the behavior. In the present study, we examined sex differences in outcome evaluation when men and women performed a “Chuck-A-Luck” dice game with a same-versus opposite-sex partner. We recruited 40 college students (Half of women) to perform the gambling game task, and measured event-related potentials (ERPs) were recorded for outcome feed back when male or female participants performed the game alone, or with same-versus opposite -sex partners. Two main findings are reported in our study. 1) FRN amplitude of same-sex condition was significantly greater than alone condition for male when the feedback was loss. However, FRN amplitude of opposite-sex condition was significantly greater than alone condition for female when feedback was loss. 2) The loss feedback induced greater P300 than gain only in alone condition. It suggests that sex differences in outcome evaluation is a complex process that is partially influenced by the partner’s sex.